Hand-mixed vancomycin versus commercial tobramycin cement revisited: A study on mechanical and antibacterial properties - Singh, Vivek Ajit; Bong, Chun Haw; Haseeb, Amber; Teh, Cindy Shuan Ju (SAGE Publications (UK and US), 2019)
Purpose: Arthroplasty-related infection has grown worldwide. Revision procedures for infection are associated with longer operating time, superior amounts of blood loss, and substantial economic encumbrance. To overcome cost, many surgeons opt for hand-mixed vancomycin into the bone cement. The objective of this research was to assess the biomechanical strength and antibacterial properties of hand-mixed vancomycin bone cement at different concentrations with commonly used industrial preblended antibiotic bone cement and plain cement. The target was to determine the ideal concentration of antibiotics that can be used in the preparation of hand-mixed vancomycin cement that delivers maximum antibiotics concentration without compromising its biomechanical properties. Materials and Methods: Vancomycin-impregnated polymethyl methacrylate (PMMA) specimen was hand prepared in varying concentrations (1–4 g). The authors tested three-point bending strength to determine ‘maximum bending load’ and stiffness and its antibacterial activity by looking into the zone of inhibition on methicillin-resistant Staphylococcus aureus-impregnated agar plate. These were compared with the industrial preblended Simplex™ P with 1 g tobramycin. Results: This study exhibited that vancomycin-PMMA disk that contained higher concentration of antibiotics had significantly higher antibacterial activity. The control group (plain cement) and industrial PMMA with preblended antibiotic (tobramycin) showed stable mechanical strength, while the hand-mixed antibiotic cement (HMAC) had variable mechanical strength varying on the concentration of antibiotics used. Conclusion: It was effectively concluded that HMAC is advantageous as a cement spacer; however, it is not recommended for primary arthroplasty and second-stage revision arthroplasty. The recommended maximum concentration of vancomycin based on this study is 2 g/pack (40 g) of cement. Industrial preblended antibiotic cement is superior to hand-mixed cement. © The Author(s) 2019.